“Métodos de fermentación en el cacao (Theobroma cacao) CCN 51 con la norma INEN 176 en la parroquia Guasaganda, La Maná” - Murillo Pilay, Murillo Pilay (2023)
Fermentation in cocoa is a very important stage in the process of obtaining the beneficiary, since from there arise the precursors of the characteristic aroma and flavor of chocolate. Currently, an ideal fermentation method has not been defined, so it is carried out poorly. For this reason, the present project proposed the evaluation of three types of fermenter with reference to the INEN 176 standard, to define the best method and removal time. A Complete Random Design (DCA) was applied with a factorial arrangement A x B; Nine treatments were obtained from the combination of factor A (three types of fermenter) and factor B (three removal times), an absolute control was included. The variables established by the INEN 176 standard were evaluated at the Centro Experimental Pichilingue (INIAP). The student Infostat program version 2020 was used to perform the analysis of variance, with a separation of means with the Tukey test (P≤ 0.05). It was obtained that the best treatments were; ladder type fermenter with removal times of 24 and 36 hours; After performing a simple effect statistical analysis for each factor, the best removal time was 36 hours, since 82.22% of grain fermentation was obtained. Finally, in terms of profitability, the best treatment was the trapezoidal type fermenter with 36 hours of removal.